2017
DOI: 10.1016/j.kjms.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of six multiplex PCR's among 200 clinical isolates of Pseudomonas aeruginosa for the detection of 20 drug resistance encoding genes

Abstract: Pseudomonas aeruginosa (P. aeruginosa) is a menacing opportunistic, nosocomial pathogen; become a growing concern as conventional antimicrobial therapy is now futile against it. Multi‐drug resistant P. aeruginosa (MDRPA) has distinctive resistance mechanisms such as production of β‐lactamases, repression of porin genes and over‐expression of efflux pumps. The focus of this study is to standardize and application of multiplex PCR (mPCR) to detect the presence of betalactamase genes encoding blaTem, blaOXA, blaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 23 publications
(31 reference statements)
6
22
4
Order By: Relevance
“…In this study significantly higher number of isolates (70.8 %) was positive for bla TEM gene. This is similar to current findings in a study in India which reported that bla TEM was the predominant gene present among the P. aeruginosa isolates (72.5 %) [9]. In that study [9], the bla OXA (33.5 %) and bla VIM (11.5%) genes were comparable.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study significantly higher number of isolates (70.8 %) was positive for bla TEM gene. This is similar to current findings in a study in India which reported that bla TEM was the predominant gene present among the P. aeruginosa isolates (72.5 %) [9]. In that study [9], the bla OXA (33.5 %) and bla VIM (11.5%) genes were comparable.…”
Section: Discussionsupporting
confidence: 90%
“…A comparable resistance to imipenem (41.1 %) and meropenem (38.9 %) was reported in China [4]. The study also reported comparable resistance values for ceftazidime (40.3 %), cefepime (38.5%) and piperacillin/tazobactam (38.9 %), while a study in India reported much lower resistance (25 %) for meropenem and comparable resistance (25 %) for piperacillin/tazobactam [9]. In contrast, a study in Brazil reported much higher degrees of resistance (64.8 %) to meropenem and imipenem in P. aeruginosa isolated from ICU patients [19].Although the majority of the isolates were resistant to gentamicin, antibiotic resistance did not differ significantly among the isolates (p = 1.00).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations